Biharmonic B-Slant Helices According To Bishop Frame In The S<(L2(R))over tilde> - Korpinar, Talat; Turhan, Essin (Soc Paranaense Matematica, 2013)
In this paper, we study biharmonic B-slant helices in the S<(L-2(R))over tilde>. We characterize the biharmonic B-slant helices in terms of their curvature and torsion. Finally, we find out their explicit parametric equations.
Keywords: Biharmonic curve; S<(L-2(R))over tilde>; curvature; torsio